A Systematic Review of the Selected Evidences on the Effectiveness of Inter-professional Education (IPE) in Developing Interprofessional Learning Environment - Said Nasser Al Harthy; Najla Al Subhi; Cyruz Tuppal; Mark Donald Reñosa (Nurse Media: Journal of Nursing, 2015)
Purpose: This systematic review aimed to provide available evidence in determining for the effectiveness of IPE as a modality in developing interprofessional learning environment for healthcare students.